TEORI GANTI RUGI DALAM PERSPEKTIF HUKUM ISLAM - Asmuni, Asmuni (Jurnal Hukum dan Peradilan, 2013)
The idea of daman towards both criminal and justice victims, from early time, has been mentioned in the nash of both Al-Quran and Al-Hadith. From the nash, Ulemas have formulated various fiqh forms concerning daman (compensation). In fact, from early time the Islamic Jurists have not applied the terms masuliyah madaniyah for justice responsibility, and masuliyah al ina'iyah for criminal one. However, several thinkers of classical Islamic law mainly al-Qurafi and al- `Iz Ibn Abdi Salam have introduced the term al-jawabir for justice conpensation (read: daman) and al-zawajir for criminal compensation (read: 'uqubah diyat, arus, etc.). Although in its development, up to recent time, Islamic Jurists often use the term masuliyah that is because of the Western work influences. Daman could occur because of deviation on akad (agreement) namely daman al-aqdi, and could happen because of violation namely daman `udwan. In determining the compensation, the esential elements are darar or lost on the victims. Darar could occur on physical, material or things and service aspects; and it could also be on moral and emotional destruction or called darar adabi including name-reputation damage. The standard for the compensation either on quality or quantity must be similar to darar suffered by the victims. Although in certain cases, the multiplying compensation may happen based on the victims' condition. Keywords: Compensation Theory, Islamic Law, Law perspectives